Adjunctive Therapies During Extracorporeal Membrane Oxygenation to Enhance Multiple Organ Support in Critically Ill Children - Canter, Marguerite Orsi; Daniels, Jessica; Bridges, Brian C. (Frontiers in Pediatrics, 2018)
Since the advent of extracorporeal membrane oxygenation (ECMO) over forty years ago, there has been increasing interest in the use of the extracorporeal circuit as a platform for providing multiple organ support. In this review, we will examine the evidence for the use of continuous renal replacement therapy, therapeutic plasma exchange, leukopheresis, adsorptive therapies, and extracorporeal liver support in conjunction with ECMO.